Effectiveness of realistic math education on mathematical problem-solving skills of students with learning disability - Sanal, Seda Ozer; Elmali, Filiz (Routledge Journals, Taylor & Francis Ltd, 2024)
The aim of this study is to investigate the effectiveness of Realistic Mathematics Education Strategies Mobile App (REMSAM) on the mathematical problem solving performance of students with learning disabilities (LD). The participants of this study consisted of five children (three girls, two boys) with LD. The study was carried out based on a multiple-baseline across-participants design. Participants' problem solving performances (understanding the problem, identifying the elements of the problem and solving the problem) were evaluated with multiple-choice tests. The findings revealed that REMSAM had a significant and positive effect on students' mathematical problem solving performances. In addition, it was determined that the students were willing to use REMSAM, the parents and teachers of the students had positive opinions about REMSAM. Future directions and limitations of the study were discussed.
Keywords: Learning disability; mathematics skills; realistic maths education; single case study